Using Problem-Based Learning as an Instructional Approach in Enhancing Problem Solving Skills between Engineering and Business - Abdul Kadir, Zulida; Hazana Abdullah, Nor; Azrol Abdullah, Rosmahalil; Ismail, Fadillah; Abdul Kadir, Adibah; A/P M.Anthony, Elizabeth (International Journal of Engineering and Technology, 2018)
Problem-based Learning (PBL) is one of an emerging student-centered approach in Malaysia. PBL has been proven to be one of the best approaches in helping students improve their soft skills. Complaints received from industry stating that many graduates are lacking of problem solving skills. Therefore, the objective of this study is to identify whether studentsâ€™ problem solving skills could be improved using PBL as an instructional tool. A quasi-experimental interrupted time series design was used involving fifty students from business and engineering faculties in a premier Technical University in Malaysia. Students were given four treatments or problems and were assessed based on accuracy and quality of solutions of the problem given. Results show that business students enhanced their problem solving skills better than engineering students. The findings support previous findings on the effectiveness of PBL on problem solving skills. This finding substantiates the use of PBL as an effective instructional tool to improve studentsâ€™ problem solving abilities.Â